Monetary policy over the life cycle - R. Anton Braun; Daisuke Ikeda (Federal Reserve Bank of Atlanta, 2021)
A tighter monetary policy is generally associated with higher real interest rates on deposits and loans, weaker performance of equities and real estate, and slower growth in employment and wages. How does a household's exposure to monetary policy vary with its age? The size and composition of both household income and asset portfolios exhibit large variation over the life cycle in Japanese data. We formulate an overlapping-generations model that reproduces these observations and use it to analyze how household responses to monetary policy shocks vary over the life cycle. Both the signs and the magnitudes of the responses of a household's net worth, disposable income, and consumption depend on its age.
Keywords: E52; E62; G51; D15; 330; monetary policy; life cycle; portfolio choice; nominal government debt